2014
DOI: 10.1039/c4md00194j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water-soluble derivatives of [60]fullerene on therapeutically important targets related to neurodegenerative diseases

Abstract: Water soluble fullerene derivatives I and II were shown to behave as promising neuroprotective agents that improve cognitive functioning in animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 37 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…The neuroprotective activity of fullerene derivatives may not be ignored either. Encouraging results of their use for the treatment of neurodegenerative pathologies (Alzheimer's and Parkinson's diseases and other diseases accompanied by cognitive impairment) leading to dementia have been demonstrated [ 39 40 ]. Moreover, it is noted that the almost nonexistent toxicity of the C 60 derivatives allows to use them in living systems without negative consequences.…”
Section: Introductionmentioning
confidence: 99%
“…The neuroprotective activity of fullerene derivatives may not be ignored either. Encouraging results of their use for the treatment of neurodegenerative pathologies (Alzheimer's and Parkinson's diseases and other diseases accompanied by cognitive impairment) leading to dementia have been demonstrated [ 39 40 ]. Moreover, it is noted that the almost nonexistent toxicity of the C 60 derivatives allows to use them in living systems without negative consequences.…”
Section: Introductionmentioning
confidence: 99%
“…The water-soluble, hydroxylated fullerene has several clinical applications, including use as a drug carrier to bypass blood ocular barriers, 31 also has been demonstrated to prevent NO-induced cytoskeletal depolymerization and nuclear damage, and to accelerate endothelial cell repair. 32,33 Moreover, neuroprotective activity of water-soluble fullerene derivatives has been reported; 34 nevertheless, we found that it was not able to enhance neuronal growth. The membrane materials chosen to build a given scaffold should exhibit multiple properties to support neuronal cell growth.…”
Section: Discussionmentioning
confidence: 63%
“…The effect of the selected constituents on MAO-B was explored by using the benzylamine deamination assay on 96-well plates. [ 25 ] A fixed substrate concentration and varying inhibitor concentrations (10–300 nM) were used to determine the higher half maximal inhibitory concentrations (IC 50 ) value at the point where 50% inhibition of the catalytic activity of the enzyme occurred. For MAO-B, the substrate concentration of 10 mM benzylamine was chosen.…”
Section: Methodsmentioning
confidence: 99%